EMPOWERMENT OF THE COMMUNITIES OF BULAKAN, CIBEBER DISTRICT THROUGH WORK COLLEGE ACTIVITIES OF BINA BANGSA UNIVERSITY STUDENTS - Fatari Fatari; Sulkiah Hendrawati; Rizkita Putri; Dinda Evitania Putri; Nur Aulia Farhani; Ilhamur Azmi (International Journal of Engagement and Empowerment, 2023)
Community empowerment in the Student Work Lecture activities carried out by group 75 students is the Bulakan sub-district community, Cibeber sub-district by providing community assistance in social, economic, health, educational, legal and religious aspects as well as appropriate technology. Student Work Lectures are field activities carried out by students for a certain period of time and are the implementation of the Tri Dharma of Higher Education. The current implementation method for Student Work Class activities is to focus more on implementing Work Programs that have been systematically arranged and empower the community. Carried out by Group 75 Students and Field Supervisors and Field Assistant Lecturers by going directly to the field to visit the community and data sources needed for questioning through direct interviews both personally and organizationally or data sources obtained through the sub-district office or office subdistrict. Results and Discussion; forming work programs, implementing work programs, implementing work programs and the role of Field Advisors and Field Assistant Lecturers. In conclusion; there is an understanding related to digital marketing specifically for entrepreneurship, there is awareness about healthy living, there is legal awareness and understands the importance of education. The creation of output as a result of Community Service